Biodigestão anaeróbia de cama de aviário com recirculação de digestato - Alcantara, Michael Steinhorst (2016)
Poultry farming has increased and so does the amount of residues from producing areas with poultry litter and dead broilers, consequently, there is a major environmental problem for the poultry industry. Poultry litter, rich in organic matter, commonly applied on soil without treatment, acidifies it by releasing hydrogen ions since it stabilizes organic matter and also because it is a nitrogen fertilizer. Therefore, other applications for poultry litter are needed and should be studied, as for example, its use for power generation by anaerobic digestion. This process is attractive for the sector by treating waste and generating biogas that may replace the energy used in poultry. There is, however, an environmental restriction to this system because it requires a large amount of water to hydrolyze poultry litter. Therefore, this study has evaluated the anaerobic digestion of poultry litter in a digester built with glass fiber boxes whose total volume was 40.0 m3. There was a system of effluent reuse from the digester to dilute its next feeding and reduce water consumption during this process. The effluent was reused with its recirculation at the feeding moment with a motor pump, in a semi-continuous system (once a day). The anaerobic digestion has been stabilized at the organic feeding charges of 0.5 and 1.0 kg total volatile solids by m3 digester, so, the evaluations 1 and 2 were created, respectively. There was a hydraulic retention time of 10 days for both evaluations. The stabilization process occurred by Shewhart charts while the process analysis occurred by the process capacity and operational energy viability of the system indexes. At the evaluation number 2, the process was capable and viable for power operations, whose energy production as methane was 4.41 times superior to the electric energy consumed on operations of the treating system, 0.0182 m3 methane kg-1 VTS-1added. The produced effluent was not characterized as an adequate biofertilizer for crop yield because it showed small amounts of nutrients content. On the other hand, the sludge is available as organic manure since a great amount of nutrients has sedimented on the bottom of the digester. At the final period, after evaluation number 2, the digester and motor pump did not present any adequate feeding flux due to the large content of solids in the effluent; so, it was not possible to operate the digester. However, pH (close to 7.00) and the ratio between volatile acidity and total alkalinity of the effluent (below 0.3) at the final period indicated that anaerobic digestion showed some potential to be continued. This fact highlights the importance of other studies about dilution of poultry litter mechanism on the effluent of digester